Por uma escuta menor - Serfaty, Gabriela (2016)
This work investigates the listening of suffering in psychiatry, taking into account its politics thickness. Such thickness proposes thinking suffering as a nomadic character that invites us to experience other kinds of suffering that are not submitted to the polarization regime, that leads, historically, the field of psychiatry. It is known that the insistence on capturing this character inside the fields of knowledge withdraws its affirmative power. This operation, performed very often by psychiatry, gives to suffering a strictly negative place, which justifies submitting it to the nomination, medicalization and "disposal", enclosing it into diagnostic categories. We can think of suffering as something invented according to the needs of each era - result of several versions, impossible to be totalized. For a minor listening takes us beyond the polarization game, inhabiting this between, which is the incorporation of biological and social, where suffering can be asserted without anchoring into a single truth. The proposal is to fish other thicknesses of psychological distress, which change according to the context, and bring news of worlds to come